EIGENFACE ALGORITHM BASED ELECTRONIC VOTING MACHINE - T., VenkataRamakoteswararao; Y., Bhaskarrao (International Journal of Psychosocial Rehabilitation, 2020)
In the process of electing a leader, the earlier system used was the ballot box, which shows false data analysis, and recently electronic voting machines are being used. In using these EV’s, the unique ID (UID) and voter ID (EID) are enough to cast the vote. But, these processes lead to enhanced fake results where the voters can vote multiple times and chances of getting tampered. Recently, so many issues and queries have been raised about the falseness of the voting system. In order to avoid these demerits, a new voting methodology where at first the unique ID is verified, then the election ID is checked, and then face recognition is performed by using the eigenfaces algorithm based on a database given by the election commission. This method gives precise results by preventing multiple votes, and authorized voters can be allowed to cast the vote.